INTERPRETASI PENGARUH HARGA, PROMOSI, KEMUDAHAAN PENGGUNAAN DAN PERILAKU KONSUMEN TERHADAP KEPUTUSAN PEMBELIAN ONLINE FOOD DELIVERY KARYAWAN GEN Z WILAYAH JAKARTA BARAT : (STUDI KASUS: GOFOOD, GRABFOOD DAN SHOPEEFOOD) - Suryani, Dita; Burhan, Aditya (Jurnal Maneksi (Management Ekonomi Dan Akuntansi), 2025)
Introduction: The purpose of this research is to examine the case study of Gen Z employees in the West Jakarta area and how online food delivery services like GoFood, GrabFood, and ShopeeFood are impacted by factors including price, promotion, ease of use, and consumer behavior. Gen Z workers in the West Jakarta area are the subject of this study. Methods: The participating companies range in size from very major corporations to very small mom-and-pop shops. Using a purposive sampling technique, 155 participants were selected for this quantitative study. A questionnaire with a Likert scale assessment is used to gather primary data. This study use multiple linear regression as its data analysis technique. The SPSS statistical program will be used to process the data. Results: The F test results demonstrate that the computed F with Sig. (0.000) < 0.05, suggesting that the factors of price, promotion, ease of use, and consumer behavior collectively impact the purchasing choices of Gen Z employees in the West Jakarta area who utilize Online Food Delivery (Case study: GoFood, GrabFood, and ShopeeFood). Studying Gen Z employees in the West Jakarta area, we find that the Price variable has a significant impact on purchasing decisions, but the Promotion variable, Ease of Use, and Consumer Behavior variables all have no significant impact. This is in relation to their use of online food delivery services such as GoFood, GrabFood, and ShopeeFood. Keywords: Price, Promotion, Ease of Use, Consumer Behavior, Purchase Decision